CHARACTERISTIC OF URINARY RETENTION IN DEPARTMENT OF UROLOGY SOETOMO GENERAL HOSPITAL SURABAYA - Wardhana, Sonny Andikha; Soebadi, Moh. Ayodhia; hardjowijoto, Sunaryo (Indonesian Journal of Urology, 2017)
Objectives: We analyze our data of patients with urinary retention that have been managed in Soetomo general hospital to know our prevalence, causes and its management. Material & methods: We retrospectively reviewed the medical records of the patients with urinary retention who admitted on our department between January 2011 and December 2012.  Results: During 2 years between January 2011 until December 2012, a total number of urinary retention was 295 cases among 1282 urology emergency cases, with sex ratio of urinary retention in men and women was 85.7% : 14.3%. Of the study population 264 (89.5%) presented with acute urine retention while 31 (10.5%) had chronic urine retention. Most of urinary retention was caused by bladder stone (33.3%) in children, urethral stricture (26.8%) in young adult men, BPH (71.3%) in elder men and cystitis (26.3%) in women. Trial of voiding without catheter (TWOC) that performed in 60 of the BPH patients, was succeeded in 43 (71.6%) of the patients and failed in 17 (28.4%). Emergency treatment of urinary retention were urethral catheter (83.7%) and cystostomy (16.3%). Conclusion: Urinary retention is one of emergency in urology that most common occur in men. Urine retention found among the participants was mainly AUR rather than CUR. Most of urinary retention was caused by bladder stone in children, urethral stricture in young adult men, BPE in elder men and cystitis in women. The most emergency management was urethral catheter. Trial of voiding without catheter showed a high success rate, so it can be considered as definitive non-surgical therapy in selective patient.